Application Development Flight Clearance Information System To Support National Airspace Security - Iryandi, Irvan; Widodo, Pujo; Santoso, Budi (Jurnal Syntax Fusion, 2025)
Every country has full and intact sovereignty over the airspace within its territory, which serves as an important foundation for the regulation and management of airspace as an integral part of the state, including Indonesia. On one hand, the vastness of Indonesia's airspace presents opportunities for management and utilization to enhance the national economy. However, on the other hand, this condition also poses significant threats, particularly regarding the use of airspace by foreign aircraft, both civilian and military. These threats include acts of terrorism, unauthorized violations of air border administration, and misuse of permits while crossing, transiting, or staying in Indonesia. The Indonesian National Armed Forces (TNI), as a state apparatus responsible for maintaining national sovereignty, actively participates in safeguarding national airspace by being involved in the issuance of Flight Clearance for unscheduled foreign aircraft operating within national airspace. Since 2011, the licensing process for unscheduled foreign aircraft has been conducted online through a management information system known as the Flight Clearance Information System (FCIS). However, the development of the FCIS application has not been maximized due to several challenges related to Human Resources (HR), facilities and infrastructure, software, and data integration that still need improvement.